Language Commodification in Culinary Businesses Naming at Sedayu City, Kelapa Gading: A Linguistic Landscape Study - Warman, Amanda Pradhitya; Widiatmoko, Sigit; Anwar, Miftahulkhairah (Bahasa Indonesia Prima, 2026)
This study examines language commodification in the naming of culinary businesses in Sedayu City, Kelapa Gading, Jakarta Timur. Employing a qualitative descriptive approach within the framework of linguistic landscape studies, this research analyzes 124 business naming units displayed on signboards, banners, and tenants, documented between January and March 2025. Data were classified into monolingual, bilingual, and multilingual forms, then interpreted through informational and symbolic functions. The results indicate that monolingual forms account for 64 data points (52%), bilingual forms for 55 (44%), and multilingual forms for 5 (4%). Indonesian remains the strongest informational anchor, while English, along with several regional and foreign languages, serves as a symbolic resource to construct modern, authentic, and exclusive brand identities. These findings suggest that language in this commercial space is no longer merely a tool for communication but has become a marketable resource used to influence consumer perception and increase exchange value. Functional analysis reveals that Indonesian dominates the informational function as a conveyor of factual messages, ensuring consumer comprehension. Conversely, in the symbolic function, the use of English and other foreign languages is leveraged to build a modern image, exclusivity, and brand appeal. Thus, the research findings demonstrate that such naming reflects a negotiation of local-global identities. Local identity is maintained as a root of authenticity, while global elements are adopted as a marketing strategy to enhance market value. Language in Sedayu City has undergone commodification, shifting its function from a mere communicative tool to an economic resource with commercial value within the dynamics of an urban commercial area.